Meaning of Jacques Lipchitz’s Organic Cubism in Relation with Juan Larrea’s Teleology of Culture - Aguirre Martínez, Guillermo (2021)
In 1954 took place in New York the first great retrospective of Jacques Lipchitz. For Juan Larrea was a perfect moment to expose his personal teleology of culture. The Open Letter to Jacques Lipchitz is the text through which Juan Larrea reveals his discoveries on the meaning of the contemporary art. According to Larrea, Lipchitz is —as himself— a prophet of the new times: his sculpture does not represent a second reality, but it reveals a higher, transparent one. The main goal is to present how Larrea took the meaning of Lipchitz’s sculpture and added it to his own worldview. In addition, this paper links all these aspects with the idea of palingenesis. This last constitutes, in Roger Griffin’s opinion, an axial point to understand the aesthetics in the first half of the twentieth century. Finally, we underline that in spite of Lipchitz —as well as Picasso— is the most outstanding artist in the eyes of Larrea, the theoretical writings of the poet defend the supremacy of a non-figurative art.